Pembangunan sistem pangkalan data bagi proses penilaian tender di dalam industri pembinaan - Yusof, Suraya (2006)
Construction industry is one of the most important industries which contribute to the development of the country. Despite the rapid development in information technology, construction industry has been slowly adopting the changes in its process. Tendering is one of important process in construction management, while tender evaluation is the most critical part to choose a trusted and qualified contractor to properly manage the project. Seems that the process involved a large amount of data and information, a systematic way by using Decision Support System, as a tool is appropriate. The first objective of this research is to study the common practice or the conventional practice in preparing tender evaluation. The second objective is to determine common problems faced by the parties responsible in preparing tender evaluation using conventional practice. Finally, a new database system will be developed by using Microsoft Access as a Decision Support System for tender evaluation process. The research methods include the information acquisition techniques, data analysis and prototype development process. While the scope in this research cover the responsible parties in tender evaluation whether in public or private sector project in Terengganu. The development of a database will provide a more systematic and structured approach in tender evaluation process.